Dynamic situation gateway based system cooperation access gatel model - Shu-hang GUO; Yu ZHANG (Tongxin xuebao)
In order to adapt the centralized access control between the application system subject and object in the envi-ronment of network configurations, a dynamic situation based system cooperation access gatel model — DSGAC was proposed. To begin with, the constitution of dynamic situational factors of access controls in the application systems of network configurations was analyzed, defining the factor of situation from muti-perspective. Furthermore, the concept of dynamic situational finite state machine was provided and a system cooperation access gatel model supporting calcula-tions and rules of the situation was presented under the constraint of dynamic situations. Finally, the real case application shows the feasibility and validation of the DSGAC model between the application systems. Additionally, the relative in-novativeness between DSGAC model and existing access control models was summerized.